Electroanalytical Determination of Danofloxacin in Biological Samples Using Square Wave Voltammetry - Chirley Vanessa Boone; Magno Aparecido Gonçalves Trindade; Claudio Teodoro de Carvalho; Adriana Evaristo de Carvalho (Orbital: The Electronic Journal of Chemistry, 2014)
The voltammetric behavior of danofloxacin (DFX) has been studied, in aqueous solution, on a glassy carbon electrode using square wave voltammetry (SWV) as electroanalytical technique. After optimization of the experimental conditions, DFX was analyzed in spiked biologic samples using a Britton-Robinson buffer with pH = 5.0 as the supporting electrolyte. Oxidation occurs at 0.98 V vs. Ag/AgCl in a two-electron process controlled by adsorption of the electrogenerated products on the electrode surface. A acceptable recovery was obtained for assay of spiked biologic samples, with value of 98.7% for the swine urine and 95.3 % for the bovine urine.